The History of Codex Alexandrinus New Evidence from Arabic Paratexts - Monier, Mina (2025)
This article re-examines Codex Alexandrinus’s history, providing new paratextual evidence that supports an Alexandrian provenance, maintained in Egypt until its 17th-century transfer to England via Constantinople. It challenges scholarship favouring Constantinople as the codex’s home until the 14th century. Analyses of endowment (waqf) statements reveal differences between Patriarch Athanasius’s waqf and codices from Constantinople. Moreover, Arabic paratexts preceding Athanasius’s waqf point to Arab-speaking Melkites in Egypt and earlier Coptic ownership. These findings, alongside distinctive features in Codex Alexandrinus’s New Testament canon paralleling Egyptian Coptic and hitherto unstudied Melkite canons, bolster a plausible Coptic acquisition and later Melkite ownership within Egyptian transmission history. The study thus presents a nuanced framework, inviting further scrutiny of the codex’s text in Greek, Coptic, and Arabic contexts. By illuminating the codex’s roots, this analysis proposes new directions for examining its attested text types.
Keywords: Manuscript; Coptic; Melkite; patriarchate of Alexandria; Provenance; Paratexts; Codex Alexandrinus; New Testament Canon